The life and works of Kahlil Gibran: a critical review - Altabaa, Homam; Hamawiya, Adham (Department of English Language and Literature IRKHS, IIUM, 2019)
There have been numerous dedicated studies on the life and works of Kahlil Gibran (1883-1931) which is understandable due to his stature and popularity in Arabic and American literatures. Nonetheless, it has been argued that the literary establishment has not given Gibran his due credit, especially in the United States, since Gibran has attained global recognition, been translated into tens of languages and sold more volumes than all other poets of America, including Walt Whitman and T.S. Eliot. This review seeks to present an overview of the studies about Gibran and highlight, when possible, the input of these studies on the spiritual aspects in his creative writings. These studies about Gibran and his works have been written in various languages, but the focus here will be on the studies published in English and Arabic, originally or in translation.